2017
DOI: 10.31189/2165-6193-6.3.42
|View full text |Cite
|
Sign up to set email alerts
|

Ambulation Orderlies and Recovery After Cardiac Surgery: A Pilot Randomized Controlled Trial

Abstract: Background: One potential strategy to increasing physical activity after surgery is to utilize an ambulation orderly (AO), a dedicated employee whose assures frequent patient walking. However, the impact of an AO on physical and functional recovery from surgery is unknown. Methods: We randomized post-operative cardiac surgical patients to receive either the AO or usual care. We measured average daily step count, changes in 6-minute walk test (6MWT) distance, and changes in functional independence (Barthel In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…6 Furthermore, we found a significant difference in the FDQ-s scores at baseline between people using a gait aid compared with those without a gait aid, indicating that the FDQ-s may be able to distinguish mobility impairments early in the postoperative course. 4,26 However, this finding should be interpreted with caution as we did not analyse the predictive utility of the new scale on the need for gait aids in the target population.…”
Section: Discussionmentioning
confidence: 91%
“…6 Furthermore, we found a significant difference in the FDQ-s scores at baseline between people using a gait aid compared with those without a gait aid, indicating that the FDQ-s may be able to distinguish mobility impairments early in the postoperative course. 4,26 However, this finding should be interpreted with caution as we did not analyse the predictive utility of the new scale on the need for gait aids in the target population.…”
Section: Discussionmentioning
confidence: 91%
“…Appropriate exercise interventions in the hospital can, at the very least, attenuate functional decline. After cardiac surgery, ambulation facilitated by “ambulation orderlies” reduced functional decline and LOS [ 22 , 37 ]. Kosse et al [ 65 ] found in their systematic review that exercise interventions (provided by physical therapists or nurses) improved performance of physical function tests, contributed to fewer discharges to post-acute care facilities, and reduced hospital length of stay in a clinically heterogeneous sample of older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The AMBULATE study is a multicenter, single-blind, parallel control design, individual-level randomized trial. It builds from our pilot trials, which demonstrated that patients with a MT ambulated more than those receiving usual care, with a small increase in mobility status, reduction in length of stay, and an increased proportion discharging home [ 36 , 37 ].…”
Section: Trial Design {8}mentioning
confidence: 99%